An Exploration of Nurses' Perceptions of the Usefulness and Easiness of Using EMRs - Anas Alhur (Journal of Public Health Sciences, 2023)
EMRs play an essential role in documenting clinical information. Nurses are integral to the success of an EMR implementation, as they are the largest group of employees in a hospital and provide patient care. A major factor in the success of EMR implementation is nurses' acceptance of the system. This study is designed to measure nurses' willingness to use EMRs in clinical practice, determine factors influencing nurses' acceptance of EMR documentation in clinical practice, and gain an understanding of the nurses' perspective on EMRs to encourage the adoption and implementation of EMRs in other health facilities in Saudi Arabia. This study included nurses from Hail General Hospital, Maternity and Children Hospital, King Khalid Hospital, and Hail General Hospital. Study results indicate that perceived usefulness and ease of use are strongly correlated, resulting in nurses' greater acceptance of EMRs. According to the study results, nurses are willing to use EMRs. Our result shows that overall, nurses find the EMR useful in their jobs, with 40.9% agreeing and 24.4% strongly agreeing. Whereas the overall easiness was 9.4% agreed and 24 strongly agreed. Nurses need to be prepared for a demanding workplace through their nursing curriculum. Nursing students and professionals should understand the importance of EMRs in ensuring high-quality, effective, and efficient patient care. It is imperative that nurses continuously improve their computer skills to keep up with technological advancements.